Issues Related to Alcohol and Substance misuse in Adolescents - Numal Kurmi1 Tafazzul Hussain Choudhury2 Bimoj Baro3, Ranjan Das4 (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
The rise in adolescent substance abuse in India is directly linked to shifting cultural values, intense competition in education and employment, increasing financial strain on families, and weakening support systems for adolescents during this transitional phase. Adolescents observe their initial exposure to different drugs, particularly easily accessible ones like glues, tobacco, cannabis, and alcohol. The most vulnerable group among adolescents consists of street children, child laborers, and adolescents with a family background of substance misuse and other emotional and behavioral difficulties at home.